Case report: Exceptional and durable response to Radium-223 and suspension of androgen deprivation therapy in a metastatic castration-resistant prostate cancer patient - Zacchi, Francesca; Carles, Joan; Gonzalez, Macarena; Maldonado, Xavier; Perez-Lopez, Raquel; Semidey, Maria Eugenia; Mateo, Joaquin (Frontiers in Oncology, 2024)
Despite the development of new therapies in the last few years, metastatic prostate cancer (PCa) is still a lethal disease. is approved for patients with advanced castration-resistant prostate cancer (CRPC) with bone metastases and no visceral disease. However, patients' outcomes are heterogenous, and there is lack of validated predictive biomarkers of response, while biomarkers for early identification of patients who benefit from treatment are limited.This case report describes a remarkable and durable response to Ra-223 in a CRPC patient with bone metastases who had rapidly progressed to many previous therapies; this response is now lasting for 5 years even after having stopped backbone androgen deprivation therapy (ADT).Here, we present the clinical course of this exceptional response, as well as comprehensive genomic and histopathology analyses on sequential biopsies acquired before and after therapy. Additionally, we review current knowledge on predictive and response biomarkers to Ra-223 in metastatic prostate cancer.